The use of IT Systems in Road Freight Transport Companies: a case study of the Greater Poland Voivodeship in Poland - Ludmiła FILINA-DAWIDOWICZ; Dorota CIESIELCZYK; Kacper GAPSKI (Communications of International Proceedings, 2025)
Nowadays, the growing interest in implementation of information technology (IT) systems in road freight transport companies is observed. Managers of transport companies search for the most appropriate IT systems striving, i.e., to save time and improve companies operation, however, implementation of such systems deals with the number of problems and barriers. Understanding the needs of transport companies representatives is crucial for the development of IT systems. The aim of the article is to identify the directions of IT systems development considering practitioners’ opinions. The case study of companies operating in Greater Poland Voivodeship in Poland was considered. A diagnostic survey was used to conduct the research, opinions of employee of transport companies operating in Greater Poland Voivodeship in Poland were analysed. The benefits and barriers to implement modern IT systems in transport companies were identified, and further assessed by transport companies representatives. Research results revealed that according to respondents’ viewpoint cybersecurity and data protection, intelligent driver assistance systems and artificial intelligence applied for data analysis are the main expected directions of IT systems development in road freight transport companies. The article is concluded with recommendations for supporting the digital transformation of analysed transport companies.
Keywords: IT systems; road freight transport; digitalization; company; development direction.